Prognostic Risk Model of Immune-Related Genes in Colorectal Cancer - Qian, Yucheng; Wei, Jingsun; Lu, Wei; Sun, Fangfang; Hwang, Maxwell; Jiang, Kai; Fu, Dongliang; Zhou, Xinyi; Kong, Xiangxing; Zhu, Yingshuang; Xiao, Qian; Hu, Yeting; et al. (Frontiers in Genetics, 2021)
Colorectal cancer (CRC) is a leading cause of cancer-related death in human. Several studies have investigated whether immune-related genes (IRGs) or tumor immune microenvironment (TIME) could be indicators of CRC prognoses. This study aimed to develop an improved prognostic signature for CRC based on IRGs to predict overall survival (OS) and provide new therapeutic targets for colorectal cancer treatment. Based on the screened IRGs, the Cox regression model was used to build a prediction model based on 18-IRGs signature. Cox regression analysis revealed that the 18-IRGs signature was an independent prognostic factor for overall survival in CRC patients. Then we used the Timer online database to explore the relationship between the risk scoring model and the infiltration of immune cells, and the results showed that the risk model can reflect the state of tumor immune microenvironment to a certain extent. In short, an 18-IRGs prognostic signature for predicting CRC patients' survival was firmly established.